The complexities of “fear” in Palestinian resistance literature: Revealing elegy as a distinct theme of Mahmoud Darwish’s poetry in qāla anā khā’if - Hafid Arsyad; Akhmad Patah (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
Numerous studies of Mahmoud Darwish's poetry concerning Palestine elucidate exile, identity, nationalism, politics, and resistance. This study offers a fresh perspective on this gem by examining another theme of Darwish, specifically elegy, as expressed in the poem Qāla Anā Khā’if. A qualitative descriptive-analytical approach was utilised to investigate data from al-Dīwān, an official repository of Arabic literary works. The data was gathered by textual authenticity, translation, close reading, and categorisation. The poet's history and the socio-political setting of the poem are deemed crucial interpretive instruments that facilitate analysis. The data analysis concentrated on the poem's linguistic and symbolic frameworks, particularly examining repetition as a literary device. The findings indicate that Darwish intensifies the complexity of fear, which encompasses fear of self, home environment, situations outside the home, loss and damage, uncertainty and losing identity, and sounds of fear. Darwish's poetry articulates the psychological and social suffering of the Palestinian people via recurring motifs, transforming it into a multifaceted experience that encompasses both personal reflection and collective strife. The poem's imagery, illustrating domestic items, urban environments, and peacefulness, underscores the idea that terror is both an inward feeling and a communal experience influenced by external factors. This study's findings enhance the corpus of Darwish and Palestinian poetry scholarship by highlighting elegy as a central topic and characteristic of Darwish’s work, alongside exile, identity, nationalism, politics, and resistance. This study solves a research gap by analysing current Arabic poetry's examination of psychological and socio-political themes, underscoring its significance in Palestinian resistance literature.